Beethoven on Beethoven: Playing his piano music his way - Newman, William S. (New York W.W. Norton & Company, 1988)
This study aims to get as close as possible to the way in which Beethoven himself would have played his piano music in both the solo and the ensemble works. These performance practices will vary according to the instrument used, tempo taken, pedalling decisions and matters of style.